SINERGI BANK SYARIAH DAN UMKM DALAM MENINGKATKAN PEREKONOMIAN MELALUI PEMBIAYAAN - Kasmiati, Kasmiati (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
Sharia banks and UMKM have been known as one of the businesses that are an important sector in the Indonesian economy. This is reflected in its resilience in facing economic turmoil in the monetary crisis that Indonesia experienced in 1998.. Therefore, this article aims to analyze the synergy of Sharia Banks and UMKM in improving the country's economy through channeled financing. This research is a type of exploratory qualitative research. Meanwhile, conclusions are drawn inductively, where data and facts obtained from the field become the reference source. Secondary data is the main data in research collected through documentation from annual financial reports officially published by the Financial Services Authority. The results of this research show that Islamic banks play a role in encouraging UMKM to improve community welfare. This can be seen from statistical data which shows that in four consecutive years, Islamic banks have distributed funds to UMKM in the form of financing amounting to 20-23% of the total financing distributed. Of these funds, 49-62% is intended for working capital needs, while the rest is designed for investment needs to support UMKM productivity in the range of 38-51%.